Comparison of the effects of probiotics, rifaximin, and lactulose in the treatment of minimal hepatic encephalopathy and gut microbiota - Wang, Ming-Wei; Ma, Wei-Juan; Wang, Yan; Ma, Xiao-Han; Xue, Yu-Feng; Guan, Jing; Chen, Xi (Frontiers in Microbiology, 2023)
Background: Minimal hepatic encephalopathy (MHE) is an early stage in the pathogenesis of hepatic encephalopathy. Intestinal microbiota is involved in the pathogenesis of hepatic encephalopathy and has become an important therapeutic target. Since there is no unified treatment principle for MHE, this study was conducted to determine the safety and efficacy of different intestinal microecological modulators in the treatment of MHE, and to explore the potential mechanism through intestinal microbiota analysis. Methods: Patients with liver cirrhosis were screened for MHE using psychometric hepatic encephalopathy score test. Patients diagnosed with MHE were enrolled and received probiotics, rifaximin or lactulose for 4 weeks. Adverse events were recorded. The psychometric hepatic encephalopathy score test was performed after treatment. Samples of blood and stool were collected at entry and 4 weeks. Blood samples were analyzed to assess blood ammonia, liver, kidney, and hemostatic functions. Stool microbiota were sequenced to confirm changes in microbial composition. Result: Of 323 patients with liver cirrhosis, 74 patients were diagnosed with MHE. In all, 54 patients were enrolled and 52 who agree to follow-up were included in analysis. The recovery rates of MHE patients received probiotics, rifaximin and lactulose were 58.8% (20/34), 45.5% (5/11) and 57.1% (4/7), respectively. Probiotics and rifaximin improved liver function in MHE patients to a certain extent. Taxonomic compositions of gut microbiota in MHE patients were distinct from healthy people before treatment; the differences were significantly reduced after treatment, and the gut microbiota gradually resembled the structure of healthy individuals. We found that the relative abundance of specific taxa associated with anti-inflammatory and good cognitive functions was increased in MHE patients after treatment. Accordingly, metabolic pathways in MHE patients were altered before and after treatment. Downregulated pathways after probiotics treatment included glycometabolism and degradation of aromatic compounds. After lactulose treatment, degradation pathways of arginine and ornithine showed a downward trend. Conclusion: Probiotics, rifaximin and lactulose are safe and effective in the treatment of MHE, and improve the composition of gut microbiota to some extent.